Kajian Eksperimen Pengaruh Penambahan Silica Fume Terhadap Sifat Adhesif Untuk Perbaikan Keramik Dinding - Dika Pratama; Rizki Febri Astuti; Mochammad Tri Rochadi; Kusdiyono Kusdiyono (Politeknik Negeri Semarang, 2018)
The release of ceramics is an undesirable event, one of the causes is the presence of trapped air which causes the area attached to the wall to decrease. To reduce this, additional ingredients / smaller silica fume additives (<1μm) can be used to fill the hollow part. The purpose of this study was to measure and compare the properties of ceramic adhesives with and without the addition of silica fume to ceramic adhesives, and to determine the percentage of addition of silica fume to obtain the most optimal adhesive strength. The method used is an experimental method in the laboratory by conducting tests of ceramic adhesion based on ASTM C 482-02 and SNI 03-4877-1998. The level of addition of silica fume used is 5, 10, 15, and 20% of the weight of cement. The test results show that there is a